Toward a consumer economy in China: implications of changing wage policies for U.S. cotton exports. (19th December 2013) - Macdonald, Stephen; Pan, Suwen; Hudson, Darren; Tuan, Francis
Abstract The effect of a Chinese minimum wage increase on China's textile market as well as on the world cotton market is evaluated. Based on a Nonlinear Quadratic Almost Ideal Demand System (NQAIDS) model of China's textile demand, the results suggest that the income elasticity for textiles is around 0.6 in China, and that apparel is less price responsive than home textiles and other textile products. Simulation results suggest that a minimum wage increase would raise Chinese domestic textile consumption and lower Chinese textile exports. Most of the decline in textile exports by China is offset by expansion in other countries' domestic textile production and results in a slight increase in world cotton mill utilization and higher clothing prices.